Inland shipping and navigation delegate information : Thursday 16 October 1997, One Great George Street Conference Centre, the Institution of Civil Engineers, London. (Thomas Telford, 1997)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 16 October 1997.
Keywords: Inland water transportation -- Congresses.; Inland navigation -- Congresses.; elektronické knihy; electronic books